Caracterização da ribonucleoproteína RBP42 no parasito Trypanosoma cruzi sob condições de estresse - Daniela de Laet Souza (2019)
RNA binding proteins (RBPs) are essential components for gene expression regulation. The interaction between RBPs and target mRNAs forms ribonucleoprotein complexes that dictate RNA fate and may aggregate into microscopically visible cytoplasmic foci in response to stimuli capable of stalling translation. In Trypanosoma cruzi, there is a large repertoire of granules that may integrate the mechanisms underlying the remarkable resistance this parasite presents to different kinds of stress. The ribonucleoprotein RBP42, frequently studied in trypanosomatids, was first described in Trypanosoma brucei as a cytoplasmic protein essential for cell viability. In this work, we characterize the protein RBP42 present in the T. cruzi CL Brener (TcbRBP42). Initially, TcbRBP42 genes and protein characteristics were studied in silico. Secondary structure predictions and conserved domain searches revealed the modular architecture of TcbRBP42. There are two structured domains, NTF2-like and RRM, linked together by an extended disordered region enriched in low complexity sequences. These characteristics were also found in its orthologues from other kinetoplastids. Additionally, only two alleles code for this protein in the parasite genome. TcbRBP42 was also characterized under the cellular stress induced by gamma radiation and benznidazole. T. cruzi presents resistance to both agents. For detection purposes, a 6His-tagged version of this protein was transfected into epimastigotes (rTcbRBP42). The rTcbRBP42 expression did not modify epimastigotes growth pattern in both normal and stress culturing conditions. The growth arrest caused by stress was very similar in transfected and wild-type epimastigotes. Immunofluorescence assays revealed that both stress conditions tested promote a differential distribution of rTcbRBP42. This protein accumulates into granular cytoplasmic structures with characteristics varying according to the kind of stress applied. Labeling of RNAs synthesized after stress induction also showed the differential effect of both treatments tested on RNA cellular distribution. After irradiation, newly synthesized RNAs do not form granules; instead, they are transported to and spread throughout the parasite cytoplasm. In contrast, after benznidazole exposure these RNAs aggregate into cytoplasmic foci. These foci were not colocalized with those of rTcbRBP42, suggesting this protein does not interact with the RNAs present in these structures. Taken together, our data suggest that TcbRBP42 is a ribonucleoprotein capable of forming granules in response to stress conditions. These structures probably vary in composition according to the kind of stress applied and may be part of the various mechanisms allowing parasite survival to the stresses caused by gamma radiation and benznidazole.